Endogenous siRNAs Derived from a Pair of Natural cis-Antisense Transcripts Regulate Salt Tolerance in Arabidopsis - Borsani, Omar (2005)
In higher eukaryotes, miRNAs and siRNAs guide translational inhibition, mRNA cleavage, or chromatin regulation. We found that the antisense overlapping gene pair of Δ(1)-pyrroline-5-carboxylate dehydrogenase (P5CDH), a stress-related gene, and SRO5, a gene of unknown function, generates two types of siRNAs. When both transcripts are present, a 24-nt siRNA is formed by a biogenesis pathway dependent on DCL2, RDR6, SGS3, and NRPD1A. Initial cleavage of the P5CDH transcript guided by the 24-nt siRNA establishes a phase for the subsequent generation of 21-nt siRNAs by DCL1 and further cleavage of P5CDH transcripts. The expression of SRO5 is induced by salt, and this induction is required to initiate siRNA formation. Our data suggest that the P5CDH and SRO5 proteins are also functionally related, and that the P5CDH-SRO5 gene pair defines a mode of siRNA function and biogenesis that may be applied to other natural cis-antisense gene pairs in eukaryotic genomes.